PAJAK DAERAH dan PENGARUHNYA TERHADAP PDRB di PROPINSI KALIMANTA TIMUR - Dwika Julia Mutiara (Signifikan: Jurnal Ilmu Ekonomi, 2015)
This  study  aims  to  see  the  influence  of  local  taxes,  retribution,  capital expenditure  and  labor  force  participation  rates  on  regional  gross  domestic product  in the District/Municipalities of East Kalimantan Province period 2004-2013. This study uses panel data by selecting best model that is the Fixed Effects Model (FEM). The results show  that the variables of local taxes and retribution have a significant effect and has positive relationship to regional gross domestic product, while capital expenditure  have no significant effect on regional gross domestic product.  For  variable  labor  force  participation  rate  (LFPR)  is  significantly influence but negative correlation to the regional gross domestic product . Based on the results obtained by the coefficient determination of 98,42% variable means of local taxes, levies, capital expenditures and LFPR in this study may explain the dependent variable is the regional gross domestic product.DOI: 10.15408/sjie.v4i1.2296